2006
DOI: 10.1177/0363546505284846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fresh Osteochondral Autografts and Allografts

Abstract: The use of fresh allograft tissue to treat osteochondral defects eliminates morbidity associated with harvesting autograft tissue without compromising the results of the surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 52 publications
(82 reference statements)
1
64
0
3
Order By: Relevance
“…Qualitatively, frozen allografts appear acellular by three months, compared with fresh allografts, which contain viable cells for as long as twelve months [12][13][14][15][16] . When compared with that in the nonoperative control knees, the confined compressive stiffness of the operatively treated knees was slightly reduced in the fresh allograft areas, and markedly reduced in the frozen allograft areas with increasing postoperative duration 12,13,15,19,20 . The reduction of cartilage load-bearing function was associated with proteoglycan content 15 ; however, other determinants of cartilage stiffness have not been investigated.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Qualitatively, frozen allografts appear acellular by three months, compared with fresh allografts, which contain viable cells for as long as twelve months [12][13][14][15][16] . When compared with that in the nonoperative control knees, the confined compressive stiffness of the operatively treated knees was slightly reduced in the fresh allograft areas, and markedly reduced in the frozen allograft areas with increasing postoperative duration 12,13,15,19,20 . The reduction of cartilage load-bearing function was associated with proteoglycan content 15 ; however, other determinants of cartilage stiffness have not been investigated.…”
mentioning
confidence: 88%
“…4 through 6). Previous allograft animal studies did not analyze depth-related variations in chondrocyte cellularity 14,15,18 and matrix content 13,14,[17][18][19][20] , which are important because chondrocytes exhibit zone-specific functions 30 . Appropriate zonal chondrocyte organization and proteoglycan synthesis rates in fresh allografts provided biological remodeling that served to preserve the articular surface, sustain bulk tissue properties (including cartilage fill, matrix content, and load-bearing function), maintain the bone-cartilage interface and underlying bone structure, and prevent progressive deterioration to graft collapse (Fig.…”
Section: Effects O F T R E At I N G Goat Articu L a R Cartilage D E Fmentioning
confidence: 99%
See 1 more Smart Citation
“…408 Th e scans will be analyzed twice by a single physician, blinded to both treatment allocation and clinical outcome, measuring completeness, thickness, and level of the subchondral plate (i.e., fl ush, depressed, or proud). 154 Additionally, bone volume fi lling of the defect aft er 1 year will be measured, and graded as good (67% to 100%), moderate (34% to 66%), or poor (0% to 33%). 288 …”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Cartilage is described as an immunologically privileged tissue, and fresh osteochondral allografts have been proved to be effective and functional for transplantation (Chu et al, 1999;Aubin et al, 2001;Williams et al, 2007;Raikin, 2009). Furthermore, a recent study showed that fresh osteochondral autograft and fresh allograft tissues are not statistically different with respect to bony incorporation, AC composition, and biomechanical properties up to six months after implantation (Glenn et al, 2006). However, this kind of treatment is limited by the scarcity of healthy grafts and the time difference between donation and clinical use, which necessitates the construction of an osteochondral allograft bank to preserve the AC that is from cadaver tissue donors or which might be manufactured by tissue engineering in the future.…”
Section: Introductionmentioning
confidence: 99%